2021
DOI: 10.1002/agj2.20764
|View full text |Cite
|
Sign up to set email alerts
|

Reducing nitrogen rate and hill distance improves rice dry matter production in saline–alkali soils

Abstract: The integrated strategies for nitrogen management and planting density are important for improving rice (Oryza sativa L.) yield in saline-alkali soil; however, the optimal growth conditions for the Songnen Plain, China, are unclear. Here, we studied the effects of nitrogen application rate (NAR) (N0, 0 kg ha −1 ; N1, 90 kg ha −1 ; N2, 120 kg ha −1 ; N3, 150 kg ha −1 ; N4, 180 kg ha −1 ) and hill distance (HD) (HD1, 16.5 cm; HD2, 13.3 cm; HD3, 10 cm) on rice dry matter accumulation, translocation, and photosynt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
(42 reference statements)
0
0
0
Order By: Relevance
“…The N uptake by rice was related to the N application rates, and N use efficiency generally decreased with an increase in the N application rate in sodic saline-alkaline rice paddies [24,31]. Our results show that with the increase in the N application rates, N uptake by rice shoot biomass increased and the N use efficiency of rice straw increased.…”
Section: Effect Of Different N Inputs On Rice Yield and N Uptakementioning
confidence: 54%
See 1 more Smart Citation
“…The N uptake by rice was related to the N application rates, and N use efficiency generally decreased with an increase in the N application rate in sodic saline-alkaline rice paddies [24,31]. Our results show that with the increase in the N application rates, N uptake by rice shoot biomass increased and the N use efficiency of rice straw increased.…”
Section: Effect Of Different N Inputs On Rice Yield and N Uptakementioning
confidence: 54%
“…However, the N use efficiency of grain increased first and then decreased, reaching the peak in the N200 treatment. The field experiment on sodic saline-alkali soil at Songnen plain by Lv et al (2021) showed that the growth rate of stems was higher under low N treatment than that under high N treatment, which is significant for improving the dry matter of stems and prevent lodging at a low N level [31]. In other words, lodging maybe cause the loss of biomass at a high N level.…”
Section: Effect Of Different N Inputs On Rice Yield and N Uptakementioning
confidence: 99%